Video Oto-endoscopic, Canalographic and Ultrasonographic Evaluation of Ear Canal in Canine Otitis Patients - S.A. Chauhan; Kiran K S; A.K. Tiwari; Y.B. Jadhav; G. S. Khandekar; Dishant Saini (The Indian Veterinary Journal, 2025)
Otitis externa is one of the most commonly presented ear affections in canine clinical practice yet highly challenging surgico-therapeutic management if root cause is undiagnosed at the earliest presentation of the case. Chronic cases make the condition even worse to be managed. This article deals with the diagnostic evaluation of the ear canals affected with acute or chronic otitis externa in dogs with special emphasis on efficient andprecise diagnostic modalities as radiography, ultrasonography and video-otoendoscopy in combination.